Risk aversion and the willingness to migrate in 30 countries - Peter Huber; Klaus Nowotny (Austrian Institute of Economic Research (WIFO), 2018)
We use individual level data covering 30 mostly post-communist and developing countries which account for over a fifth of the worldwide immigrant stock to assess the impact of risk aversion on the willingness to migrate. Consistent with theories of individual level migration decisions, risk aversion has a statistically significant negative impact on both the willingness to migrate within countries as well as abroad. This applies to virtually all countries considered and is robust across various specifications, to alternative measures of risk aversion and to different measures of the willingness to migrate. Differences in the impact of risk aversion on the willingness to migrate are also positively correlated to measures of sending country risks and the missing variable bias of omitting risk aversion from migration regressions is substantial.
Keywords: J61; R23; 330; Migration intentions; Risk Aversion; Former Communist Countries